PERENCANAAN DAN PENGANGGARAN PERUSAHAAN: KONSEP, FUNGSI, DAN IMPLEMENTASI - Muhammad Rafly Dwi Desta; Haikel Bremana Gurusinga; Taufik Hidayat (JURNAL ILMIAH NUSANTARA, 2025)
Planning and budgeting are two important aspects of business management that ensure a company achieves its goals effectively and efficiently. Planning establishes short-term and long-term strategies, while budgeting organizes the allocation of funds so that operations go according to plan. Both help companies optimize resources, avoid waste, and make data-driven decisions. This article discusses the concepts of planning and budgeting, the role of management in their implementation, and the relationship of budgeting to accounting, financial management, and business strategy. A good understanding of these aspects allows companies to be more adaptive to change and maintain financial stability in the long run.